SPECTRUM OF MAGNETIC RESONANCE IMAGING IN MOVEMENT DISORDER: Spectrum of MRI in movement disorder - Pankajbhai, Patel Dhruv; Agarwal, Beena Devi; Mohapatra, Satya Sunder Gajendra; Das, Somadatta (Student’s Journal of Health Research Africa, 2023)
Background Movement disorders share an overlapping manifestation in many cases making a clinical diagnosis alone challenging. There are no standard objective tests available for the diagnosis currently. This study attempts to illustrate the comprehensive magnetic resonance imaging (MRI) spectrum of brain abnormalities in patients with different movement disorders and to observe the agreement of clinical and radiological diagnosis. Methodology A descriptive cross-sectional study was conducted in a tertiary care teaching hospital over two years from 2020 to 2022. The study will include 50 patients with all patients with movement abnormalities were prescribed to get an MRI. Results The most commonly affected site was substantia nigra seen in 19 cases (38%), followed by midbrain in 10 cases (20%), putamen in 9 patients (18%), and caudate in 5 patients (10%). Most patients had absent swallow tail signs (38%), forming a diagnosis of Parkinson’s disease. The Hummingbird sign of PSP was observed in 6 patients (12%). Only one patient had a box-like configuration which is seen in Huntington’s disease. Clinico- radiological correlation was 72%. The diagnostic validity of the MRI in identifying movement disorders was 100% specific, with varying sensitivity for all. Conclusion MRI is currently the preferred modality for diagnosing movement disorders, owing to its ability to provide details on the structural pathologies of the brain with high resolution and sensitivity. The present study’s findings corroborated with the results of previously worldwide conducted studies. A significant agreement was observed between the clinical and radiological diagnoses.